Development of brain blood flow analysis system using near infrared spectroscopy (NIRO300®) - Kobayashi, Yoshinori; Shiga, Hiroshi; Arakawa, Ichiro; Yokoyama, Masaoki (Nihon Gaku Koukou Kinou Gakkai zasshi, 2004)
The purpose of this experiment was to develop a brain blood flow analysis system using a near infrared spectroscopy (NIRO300®) in order to clarify the effect of masticatory movement and other bodily movements on the brain blood flow. Three healthy males (26, 32, 36 years old) were asked to perform masticatory movement, finger tapping movement and opening and closing of the hand movement for 30 seconds each, and the masseter muscular activity and brain blood flow were simultaneously recorded by EMG and near infrared spectroscopy respectively. A computer program able to detect changes in masseter muscular activity and brain blood flow was developed. The measuring probe for blood flow, with the distance between irradiating part and detecting part of 4cm, was placed on the scalp over the cortical masticatory area where the responses to both the opening and closing movement of jaw and the finger movement were maximum. After these preparations, in order to confirm the setting position of the probe, a plastic capsule was placed at the mid-point between the irradiating part and the detecting part and MRI was performed. From the MRI it was confirmed that the midpoint between the irradiating part and the detecting part was set on the scalp of the area related to the movement. Also, it was possible to record and observe the masseter muscular activity and the changes in the blood flow for all subjects. The brain blood flow increased for all movements and the amount of increase was the greatest for the masticatory movement, followed by the finger tapping movement and by the opening and closing of the hand movement. Furthermore, it was found that the increase of blood flow could be quantitatively measured. The brain blood flow analysis system developed in this experiment was able to evaluate both visually and quantitatively the changes in the brain blood flow related to masticatory movement and other bodily movements.